The Role of the Systemic Immune-Inflammation Index in Predicting Postoperative Complications in Ovarian Cancer Patients: A Retrospective Cohort Study - Köse, Osman; Köse, Elif; Gök, Koray; Bostancı, Mehmet Sühha (Cancers, 2025)
Objective: Cytoreductive surgery (CRS) is the most important treatment method that increases survival in advanced-stage ovarian cancer (OC) patients. However, complications after CRS are seen as a significant cause of morbidity and mortality. Preoperative risk assessment of patients is of great importance. In recent years, inflammatory markers have been the subject of many studies evaluating malignancy and surgical outcomes. Ca125, Neutrophil–lymphocyte ratio (NLR), platelet–lymphocyte ratio (PLR), Monocyte–lymphocyte ratio (MLR), systemic inflammation index (SII), and systemic inflammatory response index (SIRI) stand out as prognostic and predictive tools in malignancies. This study aims to evaluate the preoperative inflammatory markers in patients who underwent CRS for advanced-stage epithelial ovarian cancer and to investigate the predictive power of postoperative complications. Materials and Methods: This retrospective study examines patients who underwent CRS due to advanced-stage epithelial OC at Sakarya University Training and Research Hospital between 2014 and 2023. Postoperative complications of the patients were graded according to the Clavien–Dindo classification (CDC); Ca125, NLR, PLR, SII, SIRI and MLR values were calculated using preoperative laboratory data, and the predictive values of inflammatory markers were analysed with ROC curves. Results: A significant relationship was found between complications with CDC ≥ 3 and NLR, PLR, MLR, SII, and SIRI. The AUC value of SII was calculated as 0.740 (p < 0.001), NLR as 0.719 (p = 0.001), PLR as 0.668 (p = 0.011), and SIRI as 0.651 (p = 0.022). SII stands out as the marker with the highest predictive power. SII is a strong marker in predicting postoperative complications, especially in advanced-stage OC patients. Conclusions: It was shown that preoperative inflammation markers may be an effective method for predicting postoperative complications in advanced-stage OC patients undergoing CRS. These findings may contribute to optimising surgical management and reducing complications. In future studies, these markers should be evaluated in groups with more patients, and their predictive power should be investigated.